16 - 4 [ 3 + 2 / (9 - 7)]
16 - 4 [ 3 + 2 / 2)]
16 - 4 [ 3 + 1 ]
16 - 4 [4]
16 - 16
0 <===
Answer:
13
Step-by-step explanation:
3 x 3 = 9
7 + 3 = 10
7 + ? = 3 + 7 + 3 + 7
7 + ? = 20
? = 13
Answer:
because all the fans have left
Step-by-step explanation:
Answer and Step-by-step explanation:
The computation is shown below:
Let us assume that
Spam Email be S
And, test spam positive be T
Given that
P(S) = 0.3
![P(\frac{T}{S}) = 0.95](https://tex.z-dn.net/?f=P%28%5Cfrac%7BT%7D%7BS%7D%29%20%3D%200.95)
![P(\frac{T}{S^c}) = 0.05](https://tex.z-dn.net/?f=P%28%5Cfrac%7BT%7D%7BS%5Ec%7D%29%20%3D%200.05)
Now based on the above information, the probabilities are as follows
i. P(Spam Email) is
= P(S)
= 0.3
![P(S^c) = 1 - P(S)](https://tex.z-dn.net/?f=P%28S%5Ec%29%20%3D%20%201%20-%20P%28S%29)
= 1 - 0.3
= 0.7
ii. ![P(\frac{S}{T}) = \frac{P(S\cap\ T}{P(T)}](https://tex.z-dn.net/?f=P%28%5Cfrac%7BS%7D%7BT%7D%29%20%3D%20%5Cfrac%7BP%28S%5Ccap%5C%20T%7D%7BP%28T%29%7D)
![= \frac{P(\frac{T}{S}) . P(S) }{P(\frac{T}{S}) . P(S) + P(\frac{T}{S^c}) . P(S^c) }](https://tex.z-dn.net/?f=%3D%20%5Cfrac%7BP%28%5Cfrac%7BT%7D%7BS%7D%29%20.%20P%28S%29%20%7D%7BP%28%5Cfrac%7BT%7D%7BS%7D%29%20.%20P%28S%29%20%2B%20P%28%5Cfrac%7BT%7D%7BS%5Ec%7D%29%20.%20P%28S%5Ec%29%20%7D)
![= \frac{0.95 \times 0.3}{0.95 \times 0.3 + 0.05 \times 0.7}](https://tex.z-dn.net/?f=%3D%20%5Cfrac%7B0.95%20%5Ctimes%200.3%7D%7B0.95%20%5Ctimes%200.3%20%2B%200.05%20%5Ctimes%200.7%7D)
= 0.8906
iii. ![P(\frac{S}{T^c}) = \frac{P(S\cap\ T^c}{P(T^c)}](https://tex.z-dn.net/?f=P%28%5Cfrac%7BS%7D%7BT%5Ec%7D%29%20%3D%20%5Cfrac%7BP%28S%5Ccap%5C%20T%5Ec%7D%7BP%28T%5Ec%29%7D)
![= \frac{P(\frac{T^c}{S}) . P(S) }{P(\frac{T^c}{S}) . P(S) + P(\frac{T^c}{S^c}) . P(S^c) }](https://tex.z-dn.net/?f=%3D%20%5Cfrac%7BP%28%5Cfrac%7BT%5Ec%7D%7BS%7D%29%20.%20P%28S%29%20%7D%7BP%28%5Cfrac%7BT%5Ec%7D%7BS%7D%29%20.%20P%28S%29%20%2B%20P%28%5Cfrac%7BT%5Ec%7D%7BS%5Ec%7D%29%20.%20P%28S%5Ec%29%20%7D)
![= \frac{(1 - 0.95)\times 0.3}{ (1 -0.95)0.95 \times 0.3 + (1 - 0.05) \times 0.7}](https://tex.z-dn.net/?f=%3D%20%5Cfrac%7B%281%20-%200.95%29%5Ctimes%200.3%7D%7B%20%281%20-0.95%290.95%20%5Ctimes%200.3%20%2B%20%281%20-%200.05%29%20%5Ctimes%200.7%7D)
= 0.0221
We simply applied the above formulas so that the each part could come
The distance between B and B' will be the same as distance between A and A'.
= sqrt ( (5-1)^2 + ( 1 - -2)^2)
= sqrt (16 + 9)
= 5 units answer